2018
DOI: 10.3748/wjg.v24.i25.2698
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive donor hepatectomy, are we ready for prime time?

Abstract: Minimally invasive surgery potentially reduces operative morbidities. However, pure laparoscopic approaches to donor hepatectomy have been limited by technical complexity and concerns over donor safety. Reduced-wound donor hepatectomy, either in the form of a laparoscopic-assisted technique or by utilizing a mini-laparotomy wound, i.e., hybrid approach, has been developed to bridge the transition to pure laparoscopic donor hepatectomy, offering some advantages of minimally invasive surgery. To date, pure lapar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 88 publications
1
19
0
Order By: Relevance
“…The mean difference of 116 mg had a 95% CI of 66-167 mg and was significant (P < 0.001), but NPRS in the PACU score did not differ significantly between the two groups (P = 0.573). Patients in the ODRH group had a significantly longer median postoperative hospital stay (10 [8-12] days; P = 0.003), time to the first meal after surgery (3 [2,3] days; P < 0.001), and time to JP removal after surgery (6 [5][6][7][8] days; P = 0.005), compared to patients in the PLDRH group (9 [8][9][10][11] days, 1 [1,2] day, and 6 [4][5][6][7][8] days, respectively). The respective median difference was 1 day for each comparison, and the respective 95% CIs were 0-2, 1-2, and 0-1 days.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean difference of 116 mg had a 95% CI of 66-167 mg and was significant (P < 0.001), but NPRS in the PACU score did not differ significantly between the two groups (P = 0.573). Patients in the ODRH group had a significantly longer median postoperative hospital stay (10 [8-12] days; P = 0.003), time to the first meal after surgery (3 [2,3] days; P < 0.001), and time to JP removal after surgery (6 [5][6][7][8] days; P = 0.005), compared to patients in the PLDRH group (9 [8][9][10][11] days, 1 [1,2] day, and 6 [4][5][6][7][8] days, respectively). The respective median difference was 1 day for each comparison, and the respective 95% CIs were 0-2, 1-2, and 0-1 days.…”
Section: Resultsmentioning
confidence: 99%
“…Although hand-assisted, laparoscopic, right lobe donor hepatectomy through a subxyphoid vertical incision was introduced in 2006 19 , PLDRH has only recently been attempted in a few highly specialized centers 20 . Preliminary studies of these attempts revealed that the postoperative short-term outcomes were comparable to those of the open approach 7,[9][10][11] . In particular, Kim et al demonstrated the feasibility of pure laparoscopic procedures in three donors undergoing right hepatectomies 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laparoscopic surgery is widely and diversely utilized in various surgical areas providing several advantages compared to open surgery in terms of faster postoperative recovery, shorter hospital stays, and better cosmetic outcomes 12. Laparoscopic hepatectomy has developed relatively slowly compared to other abdominal surgeries due to the long learning curve, technical difficulties, risk of bleeding and questionable long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Pure laparoscopic donor hepatectomy (PLDH) has become increasingly accepted in the minimally invasive surgery era. (1,2) Pure laparoscopic donor left lateral sectionectomy, which was first performed in 2001, (3) is now considered standard practice like the conventional open approach in highly specialized centers by international consensus. (4) However, pure laparoscopic donor major hepatectomy (PLDMH), including right and left hepatectomy, is not yet recommended widely.…”
mentioning
confidence: 99%